Eisenmenger's Syndrome in Pregnancy - Khatri, Ratna; Khatri, Devendra; Pandey, Arya; KC, Nagendra (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i2.5083 NJOG 2010 Nov-Dec; 5(2): 55-56